2000
DOI: 10.1054/bjoc.1999.1063
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of metallothionein expression with apoptosis in nasopharyngeal carcinoma

Abstract: The expression of metallothionein (MT), an intracellular ubiquitous low molecular weight protein thiol with antioxidant properties, was studied in nasopharyngeal cancer (NPC) and correlated with the apoptotic index. Immunohistochemical staining of randomly selected, formalin-fixed and paraffin-embedded normal and malignant nasopharyngeal tissues were analysed for the expression of MT using the commercially available E9 antibody directed against MT I and MT II isoforms. The corresponding apoptosis labelling ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 27 publications
1
31
0
2
Order By: Relevance
“…28 Furthermore, metallothionein I also plays a protective role against DNA damage and apoptosis induced by oxidative or external stress and has been postulated to contribute to radiation resistance in tumor cells. 29 Other genes that were also differentially upregulated in HK1 cells include the MMP-10 gene, genes encoding MCP-3, CPR2, CDK inhibitor 2A and IGF binding protein 3 (BP-3) (Fig. 1b, Table I).…”
Section: Discussionmentioning
confidence: 99%
“…28 Furthermore, metallothionein I also plays a protective role against DNA damage and apoptosis induced by oxidative or external stress and has been postulated to contribute to radiation resistance in tumor cells. 29 Other genes that were also differentially upregulated in HK1 cells include the MMP-10 gene, genes encoding MCP-3, CPR2, CDK inhibitor 2A and IGF binding protein 3 (BP-3) (Fig. 1b, Table I).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that MT-1E may participate in that role. MTs are known to influence tumour growth and survival by promoting cell proliferation and cellular repair processes, enhancing resistance to chemotherapy and inhibiting apoptosis (Kagi 1991;Kondo et al, 1995;Abdel-Mageed and Agrawal, 1997;Jayasurya et al, 2000). High MT expression has also been reported to be associated with aggressive behaviour in endometrial carcinoma (McCluggage et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…MTs are known to play putative roles in cancer cell proliferation and apoptosis (Abdel-Mageed and Agrawal, 1997;Jayasurya et al, 2000) as well as in resistance to radiation and chemotherapeutic agents (Lohrer and Robson, 1989;Yang et al, 1994, Kondo et al, 1995. In breast cancer, MT overexpression has been well documented by immunohistochemical analysis (Schmid et al, 1993;Fresno et al, 1993;Haerslev et al, 1995;Goulding et al, 1995;Jin et al, 1999), and shown to be predominantly associated with poor prognosis.…”
mentioning
confidence: 99%
“…For the detection of apoptosis in tissue sections, DNA fragmentation was identified using the terminal deoxynucleotidyl transferase-mediated, dUTPbiotin nick end-labeling (TUNEL) technique with the commercially available TdT-FragELTM DNA Fragmentation Detection kit (Oncogene Research Products) (16) in 113 tumor sections. After deparaffinization and rehydration, slides were permeabilized in 20 mg/mL of proteinase K. Endogenous peroxidase was inactivated by treating with 3% hydrogen peroxide.…”
Section: Tunel Methodsmentioning
confidence: 99%